Psychological and psychopathological sequelae in cardiovascular acute disease - Pasquale Caponnetto (Mental Illness)
The burden of mental illness is profound and growing. Each year, almost one in three adults in the non-institutionalized community has a diagnosable mental or addictive disorder, and this figure climbs to approximately 40% among emergency departments patients. We described the principal cardiovascular acute disease and their emotional and behavioral consequences where psychological intervention could improve the care pathway and clinical outcome. Peer-reviewed articles from Medline, Psycinfo, Web of Science, Scopus, and Cochrane library, about psychological and psychopathological sequelae in cardiovascular acute disease were searched. The psychological and psychopathological sequelae associated to stroke include emotional and behavioral changes and cognitive impairment. Fear, symptoms of depression, anxiety or specific post-traumatic symptoms like intrusions, hyper-arousal and/or cognitive avoidance are common in people suffering of cardiovascular acute disease treated at emergency departments. In emergency departments, health personnel must recognize psychological and psychopathological sequelae in cardiovascular acute disease in order to develop effective interventions for these patients. Identify factors that are associated with both psychological distress and physical distress and promote interventions aimed at reducing psychological distress and improving psychological health empowerment is an important element to consider in order to offer the best care to vulnerable population as that suffering of cardiovascular acute disease.